Sensing the Border at Roxham Road - Cressman, Gwendolyne (Intermédialités / Intermediality, 2019)
Roxham, a creation by Canadian photographer Michel Huneault, produced by the National Film Board (NFB), is a virtual reality project that gathers a series of 33 photographs documenting 180 irregular migrant border-crossing attempts between February and August 2017 at Roxham Road, on the Canada-US border. In order to preserve the identities of the border-crossers, the photographer shows the migrant figures in silhouette, their bodies collaged in composite images of textiles taken by Huneault during the 2015 migrant crisis in Europe. The palimpsestic layering of fabrics and voices on a three-dimensional map, which the virtual reality device allows, underscores the confusion at the border. The ontological and epistemological indeterminacy that results puts into question the representation of the border. With its emphasis on the visual, the aural, the sense of touch as well as its interactive dimension, Roxham seeks to make the experience of human beings at the border more authentic and more real, while underscoring its fundamental opacity.